2021
DOI: 10.1371/journal.pone.0251093
|View full text |Cite
|
Sign up to set email alerts
|

The spatial coupling effect between urban street network’s centrality and collection & delivery points: A spatial design network analysis-based study

Abstract: The sustainable development of collection and delivery points and urban street network is an important consideration of logistic planners. Urban street networks have a significant impact on collection and delivery points’ location, but the spatial relationship between the centrality of urban street network and collection and delivery points has not been studied using spatial design network analysis. In a multiple centrality assessment model, we used point of interest and street network data to evaluate the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In recent years, with the introduction of complexity science and the advancement of digital information technology, the network characteristics of transportation elements have become a consensus. Street centrality is an effective means to interpret the spatial characteristics of the transportation network ( 33 )—that is, the better the centrality, the better the location conditions. Therefore, the relationship between the distribution of urban social activities and economic activities and street centrality has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the introduction of complexity science and the advancement of digital information technology, the network characteristics of transportation elements have become a consensus. Street centrality is an effective means to interpret the spatial characteristics of the transportation network ( 33 )—that is, the better the centrality, the better the location conditions. Therefore, the relationship between the distribution of urban social activities and economic activities and street centrality has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Porta et al [15] and Louf and Barthelemy [56] applied this network approach to urban road networks and proposed a typology of road patterns based on their topological and geometric properties. Another study by Mehmood et al used the street network to analyze the location of logistics delivery and pick-up points in order to improve the efficiency of transport [57], while He et al examined the street network of a Chinese city for the presence and density of leisure entertainment activities [58].…”
Section: Network Approach In Urban Studiesmentioning
confidence: 99%
“…Some researchers believe that the distribution of express delivery stations could be impacted by traffic conditions: Mehmood et al (2014) argue that there is a strong correlation between express delivery stations distribution and urban street networks [37]. found that some groups take public transportation to express delivery stations [38].…”
Section: Literature Reviewmentioning
confidence: 99%